Personalized medicine in colorectal cancer: the evidence so far. (October 2012) - Gupta, Avinash; Saka, Wasir; Kerr, David J
Colorectal cancer is the third most common cancer worldwide and the fourth most common cause of cancer-related death. Current treatment continues to mostly be determined by stratifying patients into fairly broad groups, according to prognosis based on clinicopathological and histopathological staging. Conventional chemotherapy remains the mainstay of systemic treatment, with no established means of predicting response to treatment. However, greater understanding of the molecular biology underlying colorectal cancer, and the manner in which this influences prognosis and response to systemic therapy is increasingly well understood. In the future, key genetic changes in an individual patient's cancer could potentially be used to more accurately predict the risk of relapse following surgery and the likely response to systemic therapy.